Why Did the Adoption of Constitutional Deferral Lead to Unintended Consequences of Freedom of Association in Indonesia? - Andy Omara; Kristina Viri; Faiz Rahman (Sriwijaya Law Review, 2024)
A constitutional deferral is an approach utilised by constitutional drafters so that the drafters do not regulate things in detail in the constitution. This approach is believed to provide more opportunity for the constitutional framers to achieve consensus in drafting a constitution. In the end, this helps a constitution last longer. Constitutional deferral also offers some flexibility for the legislative and the judiciary in interpreting the text of the constitution in the future, which may accommodate the original intentions of the constitutional drafters. This paper argues the opposite. In Indonesia, adopting constitutional deferral causes an uncertain future of freedom of association. This paper aims to address two central questions. First, why did the framers of the first constitution adopt constitutional deferral in drafting provisions on freedom of association? Second, what are the consequences of implementing constitutional deferral toward freedom of association in Indonesia? Through historical and doctrinal approaches, the paper concludes (1) that the sharp ideological differences among constitutional drafters when drafting provisions on freedom of association forced them to employ constitutional deferral. (2) The use of constitutional deferral opens more possibilities for inconsistent interpretation by the executive, the lawmakers, and the judiciary when they establish law or adjudicated cases related to freedom of association. Through constitutional deferral, these three branches of government limit freedom of association instead of protecting such freedom.